Towards Improving Schedule Performance of Construction Projects in Uganda with Lean Construction - Abarinda, Jerusha; Kibwami, Nathan; Tutesigensi, Apollo (Association of Researchers in Construction Management., 2019)
Schedule performance of construction projects in Uganda, is wanting - most projects are not completed within their original contract durations. A growing body of research suggests that such poor performance could be addressed by implementing lean construction. However, evidence suggests that such implementation needs to be carefully designed to take contextual project environment factors into account. In this paper, we report on how lean construction can be applied to ensure timely completion of construction projects in Uganda, considering the project environment factors surrounding construction practice. The research approach that was adopted was mixed-methods, and thus involved a variety of data collection methods - participant observation, structured interviews, and questionnaires. The subjects were contractors that had ongoing projects in 2016. Construction practices were assessed, project environment factors impacting their projects identified, and their compatibility with standard lean tools assessed. The findings reveal that design changes due to inadequate initial planning were among the leading causes of poor schedule performance and that contractors lacked discipline to work within timeframes. Lean tools that were found to be applicable and thus recommended were value stream mapping to remove unnecessary processes and use of the last planner and collaborative planning tools. A strategy for integrating lean construction in the construction practice, cognizant of the environmental factors, was argued for based on the most appropriate lean tools suitable for the identified project environment factors. The research contributes to the understanding that project environment factors cannot be ignored because they affect project performance and consideration of these factors enhances effectiveness of lean construction techniques.
Keywords: lean construction, project delays, schedule performance, Uganda